Assessment of Anti-Corruption Agency of Pakistan - JAVED, DR.SAMRA (The journal of contemporary issues in business and government, 2021)
The assessment of Pakistan’s Anti-Corruption Agency, National Accountability Bureau (NAB), is a continuation of the collaborative effort initially taken by Bhutan and currently in place in other Asia Pacific countries. This report presents an analysis of Pakistan’s policy and corruption context as well as a thorough research employing the desk review of NAB’s reports, website and other relevant resources. Besides, it also presents the qualitative analysis of the interviews conducted with relevant stakeholders. The research resulted in the assessment of NAB against the set series of indicators. The assessment is followed by a series of recommendations to NAB and other relevant stakeholders including the government officials. The assessment of NAB tested 50 indictors, drafted to assess its performance, effectiveness and competence as well as to identify its weaknesses and areas for opportunity. NAB scored high in 49 per cent of the indicators assessed, moderate in 33 per cent of the indicators assessed, and low in 18 per cent of the indicators assessed. The findings indicate that two dimensions emerge out to be strong in NAB’s assessment: its Cooperation with other Organizations and its Oversight and Accountability. NAB’s Perception of Effectiveness is its weakest dimension scoring the lowest ranking. Two sets of recommendations were formulated to improve NAB’s performance. One set of recommendations were for the Government and the other set is for NAB itself.